2017
DOI: 10.1016/j.bjm.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pectin lyase overproduction by Penicillium griseoroseum mutants resistant to catabolite repression

Abstract: Expression of pectinolytic genes is regulated by catabolic repression limiting the production of pectin lyase (PL) if the natural inducer, pectin, is missing from the growth medium. Here, we report the isolation of Penicillium griseoroseum mutants resistant to 2-deoxy-d-glucose (DG) that show resistance to catabolite repression and overproduce PL. Three spontaneous and nine UV-induced mutants were obtained. Some mutants produced sectors (segments morphologically different) that were also studied. The mutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several fungal pectin lyase genes (pelA, pelB) had been isolated and characterized from Aspergillus niger (Gysler et al, 1990;Kusters-van et al, 1991;Kusters-van et al, 1992), A. oryzae (Kitamoto et al, 2001). Recently, Lima et al, (2017) reported that expression of pectinolytic genes is regulated by catabolic repression. In presence of easily available metabolites, CreA-like protein binds at the promoters of gene (5-SYGGRG-3) to inhibit the gene transcription (Kiesenhofer, 2016).…”
Section: Pectinase Producing Organismsmentioning
confidence: 99%
“…Several fungal pectin lyase genes (pelA, pelB) had been isolated and characterized from Aspergillus niger (Gysler et al, 1990;Kusters-van et al, 1991;Kusters-van et al, 1992), A. oryzae (Kitamoto et al, 2001). Recently, Lima et al, (2017) reported that expression of pectinolytic genes is regulated by catabolic repression. In presence of easily available metabolites, CreA-like protein binds at the promoters of gene (5-SYGGRG-3) to inhibit the gene transcription (Kiesenhofer, 2016).…”
Section: Pectinase Producing Organismsmentioning
confidence: 99%
“…Using submerged fermentation techniques, Antier et al 35 demonstrated that the dgrAW99-iii mutant produced 300% more pectinase than did the wild type strain Aspergillus niger C28B25. Lima et al 36 showed the enhanced pectin degradation abilities of Penicillium griseoroseum mutants (M02, M03, M04, M05, and M07) and selected sectors (M03 and M05) for pectin lyase (PL) production in liquid media due to their larger pectin degradation zones compared to those of the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Most pectin methylesterases (PGLs) degrade polygalacturonic acid and low-methoxyl pectin but exhibit less activity toward high-methoxyl pectin. In animals, the absence of endogenous pectinases hampers the digestion of pectin, making pectinase supplementation crucial for improving crude fiber utilization ( Sharma et al, 2012 ; Lima et al, 2017 ; Yang et al, 2020 ). Pectate lyase and pectin lyase act on the alpha-1,4-glycosidic bonds of pectin or pectinic acid, generating unsaturated pectin oligosaccharides without producing highly toxic methanol.…”
Section: Discussionmentioning
confidence: 99%